From heatwaves to food systems: epidemiologists addressing climate challenges - Treskova, Marina; Bärnighausen, Till; Rocha Pompeu, Cássia; Rocklöv, Joacim (International journal of epidemiology, 2024)
We are amid the Anthropocene epoch,1 observing advancing loss of biodiversity, environmental degradation and accelerated climate change. Contemporary climate change, primarily driven by anthropogenic activities, manifests as a notable increase in the average global surface temperature. In 2023, the annual mean global temperature reached a record 1.45°C above pre-industrial period.2 Fast-changing climate leads to rising sea levels, shifts in climate patterns worldwide and increased intensity and frequency of extreme weather events. Climate change threatens natural ecosystems and human health, heavily affecting the most vulnerable, and is likely to intensify over the coming years and decades. In 2023, we witnessed climatic hazards such as life-threatening heat waves across the globe3-5 and ramping wildfires in southern Europe,6 droughts in East Africa7 and exceptionally severe floods in Greece and Libya,8 accompanied by landslides triggered by the relentless downpours. Due to the current and locked-in future greenhouse gas emissions, we will continue experiencing the observed trends in natural disasters and their detrimental consequences.
Online verfügbar: 10. September 2024
Gesehen am 04.03.2025